A randomized controlled trial of the dissemination of an mHealth intervention for improving health outcomes: the WiseApp for Spanish-speakers living with HIV study protocol - Felix Olaya; Maeve Brin; Pamela Baez Caraballo; Mina Halpern; Haomiao Jia; Sergio Ozoria Ramírez; Janeth Juarez Padilla; Samantha Stonbraker; Rebecca Schnall (BMC, 2024)
Abstract Background While there is no cure for HIV, adherence to antiretroviral therapy can extend the lifespan and improve the quality of life of people with HIV. Despite the global reduction of HIV infection rates in recent years, New York City and La Romana, Dominican Republic, continue to report high infection rates among Latino populations. Many people with HIV remain virally unsuppressed in these geographic hotspots, suggesting a need for additional interventions to overcome medication adherence barriers. Tailored and culturally appropriate mobile health (mHealth) technology can be an engaging way to improve adherence. The primary objective of this trial is to test the effectiveness of an mHealth tool to improve HIV medication adherence among Spanish-speaking people living in New York City and the Dominican Republic. Methods The WiseApp study is a two-arm randomized controlled trial among 248 people with HIV across the New York and Dominican Republic sites over the course of 12 months. Participants are randomly assigned to either receive a CleverCap pill bottle that is linked to the WiseApp (intervention) or standard of care (control). All participants complete surveys at baseline, 3-month, 6-month, and 12-month follow-up visits and the study team obtains HIV-1 viral load and CD4 count results through blood draw at each study timepoint. Discussion The use of mHealth technologies to improve medication adherence among people with HIV has been implemented in recent years. Although some studies have found improvement in adherence to antiretroviral therapy in the short term, there is limited information about how these interventions improve adherence among Spanish-speaking populations. Disproportionate rates of HIV infection among Latinos in New York City suggest an existing inequitable approach in reaching and treating this population. Due to a lack of mHealth studies with Latino populations, and apps tailored to Spanish-speakers, the WiseApp study will not only demonstrate the effectiveness of this particular mHealth app but will also contribute to the mHealth research community as a whole. Trial registration This trial was registered with Clinicaltrials.gov (NCT05398185) on 5/31/2022.